Evaluating sunn hemp as a dead-end trap crop for sustainable management of the legume pod borer (Lepidoptera: Crambidae) - Yule, Sopana; Srinivasan, Ramasamy; Othim, Stephen Tarmogin Omburo (Oxford University Press, 2025)
The legume pod borer, Maruca vitrata (F.) poses a significant threat to leguminous crops, necessitating sustainable management approaches to mitigate damage and maintain productivity. This study evaluated sunn hemp, Crotalaria juncea (L.) (Fabaceae), as a potential dead-end trap crop for managing M. vitrata infestations in cowpea, Vigna unguiculata subsp. sesquipedalis (L.) (Fabaceae), and lablab bean, Lablab purpureus (L.) (Fabaceae). Laboratory oviposition assays indicated that sunn hemp was significantly less preferred than cowpea in dual-choice conditions, whereas no significant preference was detected relative to lablab bean. Interestingly, sunn hemp received more eggs than cowpea under no-choice conditions but fewer than lablab bean. Larvae feeding on sunn hemp suffered complete mortality, failing to develop beyond the fourth instar. In contrast, cowpea and lablab beans equally supported complete larval and pupal development without significant differences in developmental parameters, pupal weight, or sex ratio. Field experiments demonstrated that sunn hemp effectively reduced pest infestation relative to untreated controls, showing comparable efficacy to chemical treatments. Marketable yield proportions differed significantly between the crops, with lablab bean consistently achieving higher marketable yields than cowpea. Sunn hemp significantly enhanced the marketable yield of lablab beans, reinforcing its value as a tool for ecological pest management. Overall, sunn hemp effectively disrupted M. vitrata populations, reduced pest pressure, and improved yield quality, thus highlighting its potential as a sustainable and ecologically beneficial component in integrated pest management programs for leguminous crops.